How Business Models Are Changing in the Era of the Internet - Wałęga, Grzegorz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2016)
The development of modern information and communication technologies is changing various sectors of the economy. Commercial use of the Internet not only brought about the e-business sector, but made it a key source of competitive advantage. The article reviews the operating models of companies that base their activity on the Internet. It presents a review of the subject literature, which leads to the conclusion that new technology has increased the competitive struggle, and intensified the integration of the value chain. Most e-business models are in fact reimplementations of their traditional counterparts.